The Effect of Female CEO Presence and CEO Education on Earnings Quality: Empirical Study on All Companies Listed on the Indonesia Stock Exchange for the 2019–2022 Period - Anak Agung Istri Ita Permatasari; Gerianta Wirawan Yasa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Earnings quality refers to the accuracy of a company in presenting its earnings information. It reflects the quality of the company’s financial statements, indicating whether the reported earnings can be considered reliable or not. Earnings quality is influenced by several factors, one of which is the decision-making of the board of directors (CEO). The CEO is regarded as the most powerful individual within a company, exercising authority over corporate decisions, including the disclosure of financial information. In recent times, many women have taken on the role of CEO, and their presence is no longer underestimated. The purpose of this study is to provide empirical evidence on the effect of female CEO presence and CEO education on earnings quality. The research was conducted on all companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2022 period. The sample size was determined using a saturated sampling method, resulting in 2,792 observations. Data were collected using a non-participant observation method, and the analysis technique employed was multiple linear regression analysis. The results of this study show that female CEO presence and CEO education have no significant relationship with earnings quality.